Perfect poems, Grades 5-6 : with strategies for building fluency. (New York : Scholastic Teaching Resources, 2004)
Easy-to-read peoms with effective strategies to help students buiild word recognition, fluency, and comprehension.
Keywords: Reading -- English language -- Juvenile literature